Molecular evolution of phosphoprotein phosphatases in Drosophila. - Márton Miskei (PLoS ONE, 2011)
Phosphoprotein phosphatases (PPP), these ancient and important regulatory enzymes are present in all eukaryotic organisms. Based on the genome sequences of 12 Drosophila species we traced the evolution of the PPP catalytic subunits and noted a substantial expansion of the gene family. We concluded that the 18-22 PPP genes of Drosophilidae were generated from a core set of 8 indispensable phosphatases that are present in most of the insects. Retropositons followed by tandem gene duplications extended the phosphatase repertoire, and sporadic gene losses contributed to the species specific variations in the PPP complement. During the course of these studies we identified 5, up till now uncharacterized phosphatase retrogenes: PpY+, PpD5+, PpD6+, Pp4+, and Pp6+ which are found only in some ancient Drosophila. We demonstrated that all of these new PPP genes exhibit a distinct male specific expression. In addition to the changes in gene numbers, the intron-exon structure and the chromosomal localization of several PPP genes was also altered during evolution. The G-C content of the coding regions decreased when a gene moved into the heterochromatic region of chromosome Y. Thus the PPP enzymes exemplify the various types of dynamic rearrangements that accompany the molecular evolution of a gene family in Drosophilidae.